Can Conflict Be Planned Away? A Critical Assessment of Participatory Land Use Planning in Swedish Forest Governance - Annette Löf; Rasmus Kløcker Larsen; Felicia Fahlin (Arctic Review on Law and Politics)
A widespread governance response to land use conflict is to seek improved communication through the employment of dialogue-based instruments. In this paper, we interrogate the guiding presupposition that conflict can be planned away through a case study on the Reindeer Husbandry Plan (Renbruksplan), a tool used to address land use conflicts between industrial forestry and Indigenous Sámi reindeer herding. Drawing on critical policy analysis and environmental justice frameworks, we analyze the problematizations, silences, and effects emerging from the tool’s use in forestry planning and land use decisions. Our findings reveal that, operating in its current institutional and legal context, the tool offers limited improvements in procedural justice, exacerbates unequal distribution of burdens and benefits in terms of who gets to use forest resources, privileging a forestry-centered representation of the land use conflict. We therefore conclude that, in absence of institutional reform, the tool is likely to perpetuate conflicts and continue to reproduce the injustices embedded in Swedish forest and land use governance.